Measuring Positive Health Behaviors and Outcomes with Low Scores on MMPI–2–RF Somatic Scales. Issue 1 (2nd January 2020) - Kremyar, Andrew J.; Lee, Tayla T. C.; Ajayi, William; Friedhoff, Lesley A.; Graham, John R.
Abstract: Previous empirical studies have established that poor mental and physical health often cooccur. However, positive health behaviors and outcomes have been demonstrated to buffer against psychological dysfunction. Thus, the ability to assess for positive health behaviors and outcomes with instruments commonly used in practice, such as the Minnesota Multiphasic Personality Inventory–2–Restructured Form (MMPI–2–RF), is important. However, no study has examined the ability of MMPI–2–RF somatic scale scores to predict positive health behaviors among a healthy population. As such, in this study, we conducted correlational analyses and difference tests with 406 undergraduate students from a Midwestern university to examine whether scores on MMPI–2–RF scales assessing somatic complaints were meaningfully related to measures of health behaviors and outcomes. Results indicated high scores on the Restructured Clinical Somatic Complaints (RC1) scale and associated Specific Problems (SP) scales were meaningfully related to symptom reporting and energy level, and the SP Malaise (MLS) scale was also related to sleep quality and exercise. Additionally, low scores on RC1 and MLS were related to lack of somatic complaints and good sleep quality respectively. Overall, these findings suggest that low scores on MMPI–2–RF scales might be useful for predicting specific resilient health behaviors.